Case management in primary care for frequent users of healthcare services with chronic diseases and complex care needs: an implementation and realist evaluation protocol. Issue 11 (25th November 2018) - Hudon, Catherine; Chouinard, Maud-Christine; Aubrey-Bassler, Kris; Burge, Frederick; Doucet, Shelley; Ramsden, Vivian R; Brodeur, Magaly; Bush, Paula L; Couturier, Yves; Dubois, Marie-France; Guénette, Line; Légare, France; et al.
Abstract : Introduction: Significant evidence in the literature supports case management (CM) as an effective intervention to improve care for patients with complex healthcare needs. However, there is still little evidence about the facilitators and barriers to CM implementation in primary care setting. The three specific objectives of this study are to: (1) identify the facilitators and barriers of CM implementation in primary care clinics across Canada; (2) explain and understand the relationships between the actors, contextual factors, mechanisms and outcomes of the CM intervention; (3) identify the next steps towards CM spread in primary care across Canada. Methods and analysis: We will conduct a multiple-case embedded mixed methods study. CM will be implemented in 10 primary care clinics in five Canadian provinces. Three different units of analysis will be embedded to obtain an in-depth understanding of each case: the healthcare system (macro level), the CM intervention in the clinics (meso level) and the individual/patient (micro level). For each objective, the following strategy will be performed: (1) an implementation analysis, (2) a realist evaluation and (3) consensus building among stakeholders using the Technique for Research of Information by Animation of a Group of Experts method. Ethics and dissemination: This study, which received ethics approval, will provide innovative knowledge about facilitators and barriers to implementation of CM in different primary care jurisdictions and will explain how and why different mechanisms operate in different contexts to generate different outcomes among frequent users. Consensual and prioritised statements about next steps for spread of CM in primary care from the perspectives of all stakeholders will be provided. Our results will offer context-sensitive explanations that can better inform local practices and policies and contribute to improve the health of patients with complex healthcare needs who frequently use healthcare services. Ultimately, this will increase the performance of healthcare systems and specifically mitigate ineffective use and costs.